2018
DOI: 10.3233/jin-180089
|View full text |Cite
|
Sign up to set email alerts
|

Possible prophylactic anti-excitotoxic and anti-oxidant effects of virgin coconut oil on aluminium chloride-induced Alzheimer’s in rat models

Abstract: Alzheimer's disease (AD) is a progressive neurodegenerative disease that affects an estimated 5.4 million people worldwide. However, there remains no curative treatment for the condition. Aβ and hyperphosphorylated tau accumulation are the main hallmarks of the disease; they interfere with glutamate uptake and mediate glutamate excitotoxicity, oxidative stress, inflammation and neurodegeneration. As virgin coconut oil (VCO) is well-known as an antioxidant and anti-inflammatory natural compound, the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 68 publications
6
26
0
1
Order By: Relevance
“…The promising outcomes of this study strongly imply the possible use of VCO, not only as neuroprotective agents for those suffering from neurodegenerative diseases but also as brain food (supplements for the health populations) (Rahim et al, 2017). VCO is wellknown as an antioxidant and anti-inflammatory natural compound, VCO has a potential prophylactic effect for memory enhancement, anti-excitotoxicity, and antioxidants in the AD model (Alghamdi, 2018).…”
Section: Antioxidant Effect Of Virgin Coconut Oilmentioning
confidence: 78%
“…The promising outcomes of this study strongly imply the possible use of VCO, not only as neuroprotective agents for those suffering from neurodegenerative diseases but also as brain food (supplements for the health populations) (Rahim et al, 2017). VCO is wellknown as an antioxidant and anti-inflammatory natural compound, VCO has a potential prophylactic effect for memory enhancement, anti-excitotoxicity, and antioxidants in the AD model (Alghamdi, 2018).…”
Section: Antioxidant Effect Of Virgin Coconut Oilmentioning
confidence: 78%
“…En el estudio de Alghamdi BSA et al [4] realizado en 2018 en Arabia se evalúa el posible efecto profiláctico del aceite de coco virgen sobre el Alzheimer inducida por cloruro de aluminio en ratas. Los resultados mostraron que la administración oral de aceite de coco virgen (5 mililitros por día durante 30 días) antes de la administración del cloruro de aluminio incrementa significativamente el nivel de glutatión tanto en el hipocampo como en la corteza y disminuye significativamente el nivel de malondialdehído.…”
Section: Discussionunclassified
“…The results from the present study showed that the enhanced TH and NGF expression mediated through a number of signaling molecules and transcription factors aided by suppression of oxidative stress by VCO treatment might confer neuroprotective and anti‐inflammatory effects in the thymus and MLN. Similarly, there are reports that VCO administration can partially improve memory impairment in Alzheimer's disease models . Alterations in neuroendocrine‐immune interactions are a common feature during aging and disease pathogenesis that interferes with the healthy aging process.…”
Section: Discussionmentioning
confidence: 99%